Accidental Bowel Leakage Evaluation: A New Patient-Centered Validated Measure of Accidental Bowel Leakage Symptoms in Women. Issue 5 (May 2020) - Rogers, Rebecca G.; Sung, Vivian W.; Lukacz, Emily S.; Fairchild, Pamela; Arya, Lily A.; Barber, Matthew D.; Markland, Alayne D.; Siddiqui, Nazema Y.; Bann, Carla M.
Abstract : BACKGROUND: Questionnaires assessing accidental bowel leakage lack important patient-centered symptoms. OBJECTIVE: We aimed to create a valid measure of accidental bowel leakage symptoms. DESIGN: We previously created a conceptual framework capturing patient-centered accidental bowel leakage symptoms. The framework included bowel leakage type, severity and bother, and ancillary bowel symptoms, including predictability, awareness, leakage control, emptying disorders, and discomfort. SETTINGS: The study was conducted in outpatient clinics. PATIENTS: Women with at least monthly accidental bowel leakage were included. INTERVENTIONS: Participants completed the Accidental Bowel Leakage Evaluation at baseline and 12 and 24 weeks, as well as bowel diaries and other validated pelvic floor questionnaires. A subset completed items twice before treatment. Final item selection was based on psychometric properties and clinical importance. MAIN OUTCOME MEASURES: Psychometric analyses included Cronbach α, confirmatory factor, and item response theory analyses. Construct validity was based on correlations with measures of similar constructs. RESULTS: A total of 296 women completed baseline items, and 70 provided test–retest data. The cohort was predominately white (79%) and middle aged (64 ± 11 y). Confirmatory factor analyses supported the conceptual framework. The final 18-item scale demonstrated good internal consistency (Cronbach α = 0.77–0.90) and test-retest reliability (intraclass correlation = 0.80). Construct validity was demonstrated with baseline and 12- and 24-week scale scores, which correlated with the Vaizey ( r = 0.52, 0.68, and 0.69), Colorectal Anal Distress Inventory ( r = 0.54, 0.65, 0.71), Colorectal Anal Impact Questionnaire ( r = 0.48, 0.53, 0.53), and hygiene ( r = 0.39, 0.43, 0.49) and avoidance subscales scores of the adaptive index ( r = 0.45, 0.44, 0.43) and average number of pad changes per day on bowel diaries ( r = 0.35, 0.38, 0.31; all p < 0.001). LIMITATIONS: The study was limited by nature of involving validation in a care-seeking population. CONCLUSIONS: The Accidental Bowel Leakage Evaluation instrument is a reliable, patient-centered measure with good validity properties. This instrument improves on currently available measures by adding patient-important domains of predictability, awareness, control, emptying, and discomfort. See Video Abstract at http://links.lww.com/DCR/B172 . Evaluación de Fuga Intestinal Accidental: Una Nueva Medida Validada y Centrada en Pacientes Femeninos con Síntomas de Fuga Intestinal Accidental: ANTECEDENTES: Los cuestionarios que evalúan la fuga intestinal accidental, carecen de síntomas centrados en el paciente. OBJETIVO: Nuestro objetivo fue crear una medida válida de síntomas de fuga intestinal accidental. DISEÑO: Previamente creamos un marco conceptual centrado en el paciente, para capturar síntomas de fuga intestinal accidental. El marco incluía tipo de fuga intestinal, gravedad, molestia, y síntomas intestinales auxiliares, incluyendo previsibilidad, conciencia, control de fugas, trastornos de vaciado e incomodidad. AJUSTES: Clínicas de pacientes externos. PACIENTES: Mujeres con al menos una fuga intestinal accidental mensual. INTERVENCIONES: Las participantes completaron la Evaluación de Fuga Intestinal Accidental al inicio del estudio y a las 12 y 24 semanas, así como diarios intestinales y otros cuestionarios validados del piso pélvico. Un subconjunto completó los elementos dos veces antes del tratamiento. La selección final del elemento se basó en las propiedades psicométricas y la importancia clínica. PRINCIPALES MEDIDAS DE RESULTADO: Los análisis psicométricos incluyeron el Alfa de Cronbach, factor confirmatorio y análisis de la teoría de respuesta al elemento. La validez de constructo se basó en correlaciones con medidas de constructos similares. RESULTADOS: Un total de 296 mujeres completaron los elementos de referencia y 70 proporcionaron datos de test-retest. La cohorte fue predominantemente blanca (79%) y de mediana edad (64 +/- 11 años). Análisis factorial confirmatorio respaldó el marco conceptual. La escala final de 18 elementos, demostró una buena consistencia interna (Alfa de Cronbach = 0, 77-0, 90) y fiabilidad test-retest (correlación intraclase = 0, 80). La validez de constructo se demostró con puntajes de escala de referencia de 12 y 24 semanas que se correlacionaron con Vaizey (r = 0, 52, 0, 68 y 0, 69), Inventario de Ansiedad colorecto anal (r = 0, 54, 0, 65, 0, 71), Cuestionarios de Impacto colorecto anal (r = 0, 48, 0, 53, 0, 53) e higiene (r = 0, 39, 0, 43, 0, 49), puntuaciones de subescalas de evitación del índice adaptativo (r = 0, 45, 0, 44, 0, 43), número promedio de cambios de almohadilla por día, de los diarios intestinales (r = 0.35, 0.38, 0.31), todos p <.001. LIMITACIONES: Validación de una población en busca de atención. CONCLUSIONES: El instrumento de Evaluación de Fuga Intestinal Accidental es una medida confiable, centrada en el paciente y con buenas propiedades de validez. Este instrumento mejora las medidas actualmente disponibles, al agregar dominios importantes para el paciente de previsibilidad, conciencia, control, vaciado e incomodidad. Consulte Video Resumen en http://links.lww.com/DCR/B172 . (Traducción—Dr. Fidel Ruiz Healy ) Abstract : Supplemental Digital Content is available in the text.